(untitled) (Research, Society and Development, 2024)
Objective: The objective of this study was to carry out a literature review that addresses the use of low-level laser applied to oral lesions. Methodology: The searches were carried out on the websites: Web of Science, LILACS, MEDLINE, PUBMED, BBO databases and Google scholar using the DeCS. To produce this literature review, we used the perspective of Mattos (2015), who has a study on the different types of reviews, which served as the basis for structuring this article and which provided guidance for the methodology used. Results: Low-level laser has great potential to stimulate nerve regeneration and alleviate symptoms in patients with oral neural injury, however it is a therapy that needs urgent research in order to provide solid scientific bases to establish clearer guidelines on its use in dentistry.